The dark side of personality functioning: associations between antisocial cognitions, personality functioning (AMPD), empathy and mentalisation - Rabl, Luna; Maerz, Jeff; Viviani, Roberto; Labek, Karin (Frontiers in Psychiatry, 2024)
Introduction: With the introduction of the new psychiatric diagnostic manuals, personality functioning has gained new prominence. Several studies have reported consistent findings that individual showing high levels of antisocial features are associated with alterations in interpersonal functioning domains such as empathy and mentalisation. The focus of the current study (N = 198) is to examine antisocial cognitions, as measured by the Scrambled Sentences Task (SST), and to what extent this approach can help to better understand the relationship between antisocial traits and personality functioning/empathy. Method: We implemented a hypothesis-driven approach using logistic regression and a datadriven approach using machine learning to examine distinct but related measures of personality functioning as predictors of antisocial cognitions.Results: Antisocial cognitions were associated with low interpersonal functioning as expected, but only when not adjusting for antisocial traits, which accounted for almost all the association. The data-driven analysis revealed that individual items assessing empathic concern in personality functioning scales (as opposed to the whole scores) explained low antisocial cognitions even when adjusting for antisocial traits.Discussion: Antisocial cognitions appear to be associated to two distinct traits, the antisocial and a specific type of personality functioning. This finding is discussed in terms of the possible distinction between two motivational forces: to harm others/prioritize one's advantage, and to help suffering others.